Motivations for ISO 9001 quality management system implementation and certification – mapping the territory with a novel classification proposal - Fonseca, Luís Miguel (2021)
This paper aims to identify and characterize the motivations for ISO 9001 quality management system (QMS) implementation and certification, with a novel, valid and business-oriented scale applied to a large sample. Instead of adopting a normative approach focusing on the internal/external nature of the motivation, this investigation aims to emphasize the ISO 9001 driving forces from an instrumental (productivity, market and competitiveness) perspective. This study is framed with a quantitative methodology supported by an email survey encompassing a sample of 526 Portuguese ISO 9001 certified organizations. Descriptive statistics, exploratory factorial analysis (EFA), t-tests and correlation analysis were performed according to the proposed research questions. Regarding the motivations, three factors were obtained by applying EFA: market, productivity and competitiveness. The respondent organizations consider the productivity factor (mainly related to internal motivations) to be the most important. Concerning the other factors, competitiveness in the sector is ranked second and the reasons related to the market come in third. Additionally, organizations of medium dimension (between 50 and 249 employees), certified up to 1999 or from the private sector, give greater relevance to motivations related to the market and competitiveness.